G.R.O.W Project: Development of a Technical Manual for Sustainable and Educational Cultivation in Governador Mangabeira - Alessandra Cardim; Gabriela Lopes; Mauro Reis; Nathalya Barros; Sara do Vale; Clariane Teixeira Pessoa Mamona; Pietro Carlos Gonçalves Conceição (JOURNAL OF BIOENGINEERING, TECHNOLOGIES AND HEALTH, 2026)
This study presents the G.R.O.W Project, an educational and technological initiative designed to strengthen sustainable agricultural practices in school and family gardens within the municipality of Governador Mangabeira, Bahia, Brazil. Addressing a socio-environmental context marked by land fragmentation, soil degradation, and limited access to agroecological knowledge, the project integrates the disciplines of geography, chemistry, and mathematics to develop low-cost, replicable solutions for food production and environmental education. Methodologically, the study employed an ethnoscientific approach, combining participatory observation, informal interviews, and bibliographic research to document local agricultural practices and integrate traditional knowledge into technical recommendations. The resulting manual details strategies for soil preparation, crop layout optimization, automated drip irrigation using Arduino-based moisture sensors, rainwater drainage systems, and ecological pest control through botanical extracts and biological competition. Experimental implementation demonstrated the technical and economic feasibility of these systems, with an estimated total cost of R$ 338.34, significantly lower than conventional alternatives, while ensuring water efficiency and crop productivity. The proposed solutions directly support food security, promote environmental preservation, and enhance community autonomy, positioning the school as a hub for rural innovation and socio-environmental transformation.